The Impact of Electronic Recruitment towards Employer Branding through Candidate Experience (Survey on Recent Graduates of Business Administration, Faculty of Administrative Science, University of Brawijaya Batch 2013) - Nabila Zahrudini; Tri Wulida Afrianty (Wacana Journal of Social and Humanity Studies, 2020)
Electronic recruitment has emerged as a preeminent way for job seekers to apply for a job. The use of technology in the recruiting process has made the relationship between candidates and companies shifted as the inadequacy of personal interaction occurred, impacting the way candidates see their potential employer. This research identified the influence of Electronic Recruitment on Employer Branding, the influence of Electronic Recruitment on Candidate Experience, the influence of Candidate Experience on Employer Branding, and the influence of Electronic Recruitment on Employer Branding through Candidate Experience as a mediating variable. The type of this research is explanatory research with a quantitative approach. The sample of this research is recent graduates of Business Administration, Faculty of Administrative Science, University of Brawijaya Batch 2013 that has gone through the electronic recruitment process. The sampling technique used for this research was using purposive sampling and the data collection method done by distributing the online questionnaire to 60 respondents according to the sampling criteria. The data then analyzed using descriptive statistical analysis and path analysis. The result showed that Candidate Experience proved to be the mediating variable of Electronic Recruitment and Employer Branding.